OBESITY CHILDREN IN STUDENTS AT ARACAJU CITY (Fiep Bulletin - online, 2014)
The obesity is one of the illnesses that nowadays high level of growth in the world presents. In Brazil according to Brazilian Institute of Geography and Statistics 13% of the women, 7% of amazing men and 15% of the children are obeses. In the opinion of specialists some reasons can lead to the obesity, amongst them the sedentary and the bad alimentary habits are the main ones. The objective of this study was to determine and to compare the anthropometrics measures and the percentage of fat in students of the public and private school. 160 children between 7 to the 10 years of age had been evaluated. The anthropometrics evaluation consisted of the weighing and measure of the stature. The percentage of fat was gotten through the protocol of Slaughter(1988). The results had demonstrated that the students of the private school had presented themselves with raised height and weight more of the one than the pupils of the school publishes. In the evaluation of the percentage of fat the pupils of the public net had presented the percentages lowest. Of this form we can conclude that the lesser values of corporal weight and height observed in the children of the school publish suggest a deficit in its development. With relation to the percentage of fat we observe that the children of the private school had presented higher average values, concluding that these have a bigger predisposition to develop futures problems with the obesity.
Keywords: anthropometry; percentage of fat; obesity